2019
DOI: 10.1590/1413-7054201943023019
|View full text |Cite
|
Sign up to set email alerts
|

Silicon foliar application attenuates the effects of water suppression on cowpea cultivars

Abstract: Silicon and proline play important physiological, metabolic and functional roles in plants, especially under water deficit conditions. Their application can mitigate the adverse effects of stress in crops by increasing water use efficiency and antioxidant activity. The objective of this study was to evaluate silicon (Si) as attenuator of the effects of water deficit on cowpea cultivars, through physiological, biochemical and growth indicators. The experimental design was randomized blocks with four cultivars (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
17
1
Order By: Relevance
“…The proline (Pro) leaf concentration was higher in the WD condition and differed only as a function of FC (Figure 1d). The general strategy of plants for maintaining water in WD conditions is an osmotic adjustment, due to the accumulation of osmolytes (Chaumont;Tyerman, 2014;Nawaz et al, 2016;Silva et al, 2019). However, there was no differential osmotic adjustment due to the spraying of KPhi, NaHS, and ZS in the present study, which was observed in the results of osmotic potential (Ψ S ) ( Figure 1c), with only an effect of the imposed water regimes.…”
Section: Resultscontrasting
confidence: 42%
“…The proline (Pro) leaf concentration was higher in the WD condition and differed only as a function of FC (Figure 1d). The general strategy of plants for maintaining water in WD conditions is an osmotic adjustment, due to the accumulation of osmolytes (Chaumont;Tyerman, 2014;Nawaz et al, 2016;Silva et al, 2019). However, there was no differential osmotic adjustment due to the spraying of KPhi, NaHS, and ZS in the present study, which was observed in the results of osmotic potential (Ψ S ) ( Figure 1c), with only an effect of the imposed water regimes.…”
Section: Resultscontrasting
confidence: 42%
“…Proline accumulation is compatible with osmoprotective strategies, that is, it is regulated between source and sink organs in the plant similarly, regardless of the genotype (Zegaoui et al, 2017). In cowpea under water restriction, proline synthesis induction can increase the osmolyte concentration by more than 100% (Silva et al, 2019;Andrade et al, 2021), which confirms its importance in maintaining the cell water status of this species.…”
Section: Cowpea Development and Metabolic Changes Under Water Deficitmentioning
confidence: 66%
“…In cowpea, the water potential of tissue is reduced under water deficit conditions, which decreases cell turgor (Goufo et al, 2017;Merwad et al, 2018;Silva et al, 2019). During water stress, the decline of leaf water potential alters the permeability and sustainability of the membranes and interferes with the regular plants' functions mainly due to osmotic and redox system imbalance, which causes losses in the developing organs during the growth stage (Silva et al, 2019). As a result of the oxidative stress, an increment in lipid peroxidation is observed in cowpea under water restriction, mainly due to the overproduction of hydrogen peroxide (H 2 O 2 ).…”
Section: Cowpea Development and Metabolic Changes Under Water Deficitmentioning
confidence: 99%
See 2 more Smart Citations